Steeds of the gods - Coats, Lucy (Coats, Lucy. Beasts of Olympus, 2015)
"Demon, the official Olympian beast keeper, is caught between Helios and Poseidon, who are planning a race to see which of their steeds is the fastest, but both vengeful gods have requested Demon's help, and he can choose only one"--